Diretas Já e autocracia burguesa no Brasil: luta política na transição conservadora - Silva Junior, Samuel Fernando da (2018)
The purpose of this dissertation is to study the movement Diretas Já in Brazil, which took place during the years 1983 and 1984, in the midst of the political transition. For this analysis, it was necessary to make a digression about the model of economic and political development under which Brazil was inserted, seeking to highlight the antipopular and autocratic form of internal, dependent and subordinate modernization in its external relation, engendered by the colonial way of development , as well as its model of social organization based on rearrangements and political recompositions by the top in an unpopular and antipopular way. The corollary of this kind of development was what Gramsci called the passive revolution of regressive content, also known as the restoration revolution, a process permanently crowned in Brazil in its peripheral insertion to imperialism and to international development guidelines. In this way, we can understand in a more substantial way the importance and the sense that the Diretas Já already taken in the transition process. Another point necessary for the broader understanding of the movement by the Diretas is the rebuilding of the bloc in power that began in 1974 and intensified through successive crises – the exhaustion of the economic miracle, First (1973) and Second Oil Crisis (1979). This recomposition can be noticed from the reestablishment of alliances between the Brazilian businessmen who were beginning to envisage a transition process, but who did not lose both their privileges and the high rate of exploitation of the workforce at the same time. Faced with the economic crisis, these entrepreneurs, especially the so-called "new entrepreneurs" (the Gerdau, Ermírio de Morais, Setúbal, Diniz, among others) allied themselves with the "opposition economists" and with the PMDB opposition sectors around a "new" developmentalist project for the succession process. It is through this internally and externally embodied recomposition (by political and economic influences of Samuel P. Huntington and David Rockefeller) that we understand the possibilities and limits of the movement for immediate suffrage. Some hypotheses and conclusions that circumscribe the present research which can be presented in advance are: a) that the movement for the Diretas Já already had two different orientations between the years 1983 and 1984: in the first year marked mainly by the antiautocratic tensioning led by PT, CUT and base movements, and in the second by the anticesarist perspective hegemonically ruled by the PMDB, PDT and PDS dissidents; b) that the movement by the Diretas was only possible and relatively consistent (duration of about 15 months) by the permanent correlation of forces impressed within the movement between the antiautocratic and anticesarist opposition; c) that the Diretas Já already taken concrete and practical form with the PT's performance in 1983, culminating in the mobilization of November 15, 1983 in the Charles Muller square in São Paulo, forcing the PMDB to participate effectively in the movement, both to neutralize the anti-autocratic leadership as to acquiring political and electoral dividends, albeit in a disguised way; d) that the movement for the Diretas no longer ended with its defeat on April 25, 1984, when rejection of the amendment Dante de Oliveira in the Chamber of Deputies, as seen in the literature that sought to deal with the subject, but was led to carried out exclusively by the antiautocratic opposition and by cadres to the left of the PMDB under the mantle of the amendment Theodoro Mendes; e) that there was a dispute over the "paternity" of the pro-Diretas movement after its defeat between the consensus-building sector in the Electoral College, the pro-Tancredo movement and the Democratic Alliance, and the antiautocratic sector gathered around the amendment Theodore Mendes. This "paternity" was arbitrarily attributed to the pro-Tancredo movement by the media as a whole, relegating the pro-direct movement led by the antiautocratic opposition to oblivion. These are some of the hypotheses that surround the present research, and can only be answered with greater argument when we understand, historically, that is, vertically and horizontally, the Brazilian development model and its successive political recompositions, so that we can contrast that the Diretas, despite the successive limits imposed by the bourgeois opposition, was a privileged locus of political dispute; its existence as well as its contribution to the change in the correlation of forces is due to the participation and resistance of the popular movement led by the antiautocratic opposition, since they stressed that the political transition was "not given", that is, it could be modified, albeit partially, through political struggle.. Finally, the background of this research is to understand how the bourgeois autocracy is configured and institutionalized before the movements of political struggle in Brazil.